A novel method for synthesis of polyaniline and its application for catalytic degradation of atrazine in a Fenton-like system. (April 2018) - Wang, Chao; Guo, Zupei; Hong, Ran; Gao, Juan; Guo, Yong; Gu, Cheng
Abstract: Recently, polyaniline (PANI) has received widespread attention for the free volume, optical transmittance and electrical conductivity. In this study, a chemical vapor deposition method was developed to synthesize the conductive PANI-clay composite catalyzed by Fe(III)-saturated attapulgite (Fe(III)-ATTP). The reaction is initiated by the electron transfer from aniline (ANI) to Fe(III), subsequently generating ANI radical cation. The radical could further polymerize and form PANI in the constrained micropore structure of ATTP. The Raman, Fourier transform infrared and X-ray photoelectron spectra confirmed the formation of PANI on Fe(III)-ATTP surface by comparison with the PANI standard. The newly synthesized Fe(III)-ATTP-PANI composite exhibited superior reactivity as indicated by the efficient dissipation of atrazine in the presence of hydrogen peroxide (H2 O2 ), and the degradation rate increased up to almost 150 times compared to Fe(III)-ATTP. The higher reactivity of Fe(III)-ATTP-PANI/H2 O2 system was attributed to the accelerated electron transfer, the formation of ferrous ions, and the enhanced adsorption of atrazine onto attapulgite. Furthermore, our experimental results demonstrated that Fe(III)-ATTP-PANI showed good stability and it could be reused for several reaction cycles with high reactivity. This new material could act as an environmental-friendly catalyst in Fenton-like reaction system and show promising potential to effectively eliminate many persistent organic contaminants. Graphical abstract: Image 1 Highlights: A CVD method is used to synthesize the conductive PANI catalyzed by Fe(III)-ATTP. The Fe(III)-ATTP-PANI composite shows superior reactivity in atrazine degradation. Conductive PANI, Fe(II) formation and adsorption can promote the degradation. Fe(III)-ATTP-PANI shows good stability and can be reused for at least six cycles.